Perancangan Sistem Informasi Automatic Capture Tool dengan Metode Analisa Cost Benefit - Rasam, Rasam; Amsury, Fachri (Program Studi Sistem Informasi, Universitas Multi Data Palembang, 2024)
Technology has an impact on the evolution of the business world, which can affect how to plan, control and evaluate business activities, as is the case with Adira Finance. Adira Finance has used the Monitoring Application to monitor the running application system, namely the ELK Tools (Elasticsearch Logstash and Kibana). ELK can capture existing data on the server, be it CPU usage, database, network, and so on. ELK can provide a warning if there is a failure or error in the application system used. However, the current solution team only analyzes data after a failure or error, cannot analyze data before the incident. For this reason, implementation of automation capture is carried out using Selenium WebDriver to assist in capturing automatic monitoring results earlier before system failure occurs. The analysis was carried out by applying the cost benefit analysis method. The result of this implementation is a bot that can automatically capture and send the results to the telegram group in Adira Finance. Companies can consider whether the implementation of this automation for repairs or improvements to the monitoring system performance management is acceptable or not